Zinc oxide (zno), magnesium hydroxide [mg(oh)2] and calcium carbonate (caco3) filled hdpe polymer composites: mechanical, thermal and morphological properties - Ersoy, Sezgin; Taşdemir, Münir (Marmara Üniversitesi Fen Bilimleri Dergisi, 2012)
Polymer nanocomposites represent a new alternative to conventionally filled polymers. Because of their nanometer sizes, filler dispersion nanocomposites exhibit markedly improved properties when compared to the pure polymers or their traditional composites. These include increased modulus and strength, outstanding barrier properties, improved solvent and heat resistance and decreased flammability. In this study, mechanical, thermal and morphological properties of the high density polyethylene (HDPE) composites filled with nano zinc oxide ZnO), magnesium hydroxide [Mg(OH)2]and calcium carbonate (CaCO3) were investigated. The structure and properties of the composites are characterized using a scanning electron microscopy (SEM) and Energy dispersive X-ray spectroscopy (EDS). Furthermore, HDPE composites were subjected to examinations to obtain their tensile strengths, yield strengths, elasticity modulus, % elongation, Izod impact strength, hardness, wear strengths, heat deflection temperature (HDT),Vicat softening point and melt flow index (MFI).
Keywords: Magnesium hydroxide; calcium carbonate; zinc oxide; high density polyethylene; polymer composites